Typification of the name Astragalus vulnerarioides, basionym of Anthyllis vulneraria subsp. vulnerarioides (Fabaceae), and notes on its distribution - Conti, Fabio; Guglielmone, Laura; Pennesi, Riccardo; Bartolucci, Fabrizio (Phytotaxa, 2016)
Astragalus vulnerarioides Allioni (1785a: 343) was first described from Mt. Cenis, between the Cottian and Graian Alps (western Alps, France), probably based on herbarium specimens collected by Allioni. The author cited two illustrations in the protologue, which are consequently original material for the name (Art. 9.3 of the ICN, McNeill et al. 2012). The illustrations were drawn by F. Peyrolery. The first was published in the third volume of Flora Pedemontana (T. XIX, Fig. 2, Allioni 1785b), while the second is an unpublished illustration from the Iconographia Taurinensis (Vol. XV, T. 79, Fig. 2, 1765), a collection of watercolours from the 18th and first half of the 19th centuries, housed in the Library of the Department of Plant Biology of the University of Torino (Forneris 2008). Both these illustrations match Allioni’s’ diagnosis, were cited in the protologue and correspond to the current concept of the species.